PENGARUH KOMPENSASI DAN PELATIHAN TERHADAP KINERJA PEGAWAI - AMIRULLAH -; AWIK KHOLIDAH (Jurnal Akademika, 2019)
This study aims to analyze and explain the Effect of Compensation and Training on Employee Performance. This research was conducted using a survey method for employees at the UB's Faculty of Agriculture Malang with a total sample of 56 respondents. The analytical tool used is multiple linear regression analysis. The results showed that compensation and training simultaneously had a significant effect on employee performance. Compensation and Training partially have a significant effect on employee performance. Partially, the compensation variable has a dominant effect on employee performance. Keywords: Compensation, Training, Employee Performance